A growing concern for meaning: Exploring the links between ego development and eudaimonia - Osin, Evgeny N.; Voevodina, Elena Yu.; Kostenko, Vasily Yu. (Frontiers in Psychology, 2023)
Introduction Eudaimonia, in contrast to hedonia, is theorized to be a more complex type of positive functioning that involves personal growth and is guided by the pursuit of meaning. However, the existing evidence linking eudaimonia to personality development is rather scarce. To fill this gap, we aimed to explore whether ego development is related to eudaimonic well-being and eudaimonic orientations, most notably, the concern for meaning: we explored both the quantitative differences in the presence of meaning and the search for it, as well as qualitative differences in lay theories of meaning. Methods Russian-speaking volunteers recruited online (N = 364, aged 18 to 85, 63% female) completed measures of ego development (Washington University Sentence Completion Test), meaning in life (Meaning in Life Questionnaire), lay theories of meaning (and original 20-item measure), hedonic and eudaimonic motives for activities (HEMA), and well-being (Mental Health Continuum—Short Form). Results Ego development emerged as a weak, but significant positive predictor of well-being and this effect was fully mediated by the presence of meaning and eudaimonic motives. Latent profile analysis of the items tapping into lay theories of meaning revealed four distinct individual approaches to meaning that mainly differed in the subjective importance and salience of meaning. Participants with stronger concern for meaning revealed higher scores on ego development, both presence and search for meaning, eudaimonic motives, and well-being. Discussion The results add to the evidence concerning the links between ego development and well-being and are in line with the theoretical view of eudaimonia as a process of growth guided by personal concern for meaning. The findings suggest that eudaimonia might be more easily attained by individuals at higher stages of personal development.